Factuality and Impartiality in the Reporting of Sexual Violence Against Children at Kompas.com and Tribunnews.com - Sugianto, Larasati Indhita; Nuraeni, Reni (Journalism Study Program, Faculty of Communication Sciences, Universitas Padjadjaran, 2023)
During the pandemic, the issue of sexual violence against children in Indonesia reached 10,328 cases. One form of media that can be a source of information in Indonesia are news portals. The media should carry out objectivity in publishing news about sexual violence. News pertaining to sexual violence against children has been highlighted by the media; among them are Kompas.com and Tribunnews.com. This study aims to determine the level of factuality and impartiality of news portals in producing news content on sexual violence against children. Researchers use a quantitative approach with a descriptive nature. In this study, researchers looked at each indicator, including the level of truth, relevance, balance, and neutrality, by Westersthal's concept of objectivity. Researchers use a positivistic paradigm and descriptive content analysis research method. The results showed that the level of truth in the news on Tribunnews.com is higher while Kompas.com has not fulfilled the news with 5W + 1H, Kompas.com still has not fulfilled the level of relevance while Tribunnews.com has fulfilled the level of social reality and the audience so that the news is not subjective. At the level of balance, Kompas.com and Tribunnews.com still tend to report the perpetrator's point of view, and Tribunnews.com still uses hyperbolic language in processing news. In assessing factuality and impartiality, Kompas.com and Tribunnews.com still do not meet the objective requirements in producing news of sexual violence against children.